Effects of interface roughness on the annealing behaviour of laminated Ti-Al composite deformed by hot rolling. Issue 1 (July 2015) - Du, Y; Fan, G H; Yu, T; Hansen, N; Geng, L; Huang, X
Abstract: A laminated Ti-Al composite has been fabricated by hot compaction and hot rolling of alternate layers of commercial purity Ti and Al sheets with a thickness of 200 μm. The hot compaction temperature was 500°C and in a following step the composite has been reduced 50% in thickness by hot rolling. The fully consolidated composite has been annealed at 300°C and 500°C for different length of time. As a result of the differences in crystal structure and mechanical properties between Ti and Al protrusions and retrusions formed at the interface. A heterogeneous interface has thereby been created. The heterogeneity affected the recovery kinetics of the aluminium phase which at 300°C was faster near the interface than in the middle of the Al layer. This effect of a heterogeneous interface is of relevance when optimizing the thermomechanical processing of the composite to obtain high strength and formability for application.